Islamic Parenting Pengasuh Ribath Hidayatul Qur’an sebagai Orang Tua dalam Perkembangan Akhlaq Santri Pondok Pesantren Darul Ulum - Rifqi Andika Maula Fatahna; Mahmud Huda; Mochamad Samsukadi (Indo Publishing, 2026)
This study aims to analyze the pattern of Islamic parenting implemented by the caregivers of Ribath Hidayatul Qur’an at the Darul Ulum Islamic Boarding School in Jombang, as well as its influence on the moral development of the students (santri). The research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The findings indicate that the Islamic parenting applied encompasses parenting from the prenatal stage, the inculcation of moral values through role modeling, a religious environment, and habituation methods based on the principles of the Qur'an and Hadith. This parenting pattern significantly shapes students’ character to be morally upright (akhlaqul karimah) and spiritually aware. The conclusion of this study is that the role of the caregiver as a parental figure in the pesantren has a substantial impact on the holistic development of the students’ character.